2001
DOI: 10.4049/jimmunol.166.8.4822
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Evidence for a Signaling Partnership Between Urokinase Receptors (CD87) and L-Selectin (CD62L) in Human Polymorphonuclear Neutrophils

Abstract: Leukocyte urokinase plasminogen activator receptors (uPARs) cluster at adhesion interfaces and at migratory fronts where they participate in adhesion, chemotaxis, and proteolysis. uPAR aggregation triggers activation signaling even though this glycolipid-anchored protein must associate with membrane-spanning proteins to access the cell interior. This study demonstrates a novel partnership between uPAR and L-selectin in human polymorphonuclear neutrophils. Fluorescence resonance energy transfer demonstrated a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 28 publications
(28 reference statements)
1
24
0
Order By: Relevance
“…Therefore, it is conceivable that uPAR is modulating either selectin binding or function of the ␣4 integrin in this model. Neutrophil uPAR has recently been shown to associate with L-selectin on the cell surface, although the functional significance of this is not known (40). Because we have shown that Ab blockade of L-selectin on the lymphocyte cell surface had no effect on lymphocyte recruitment to the lung in this model (17), uPARmediated modulation of L-selectin function is an unlikely mechanism for diminished recruitment of uPAR Ϫ/Ϫ lymphoblasts.…”
Section: Resultsmentioning
confidence: 77%
“…Therefore, it is conceivable that uPAR is modulating either selectin binding or function of the ␣4 integrin in this model. Neutrophil uPAR has recently been shown to associate with L-selectin on the cell surface, although the functional significance of this is not known (40). Because we have shown that Ab blockade of L-selectin on the lymphocyte cell surface had no effect on lymphocyte recruitment to the lung in this model (17), uPARmediated modulation of L-selectin function is an unlikely mechanism for diminished recruitment of uPAR Ϫ/Ϫ lymphoblasts.…”
Section: Resultsmentioning
confidence: 77%
“…Considering our results, we hypothesized that the mitogenic activity of uPA is mediated via integrins adjacent to uPAR. It was reported by Sitrin et al that integrins and uPAR are associated via carbohydrate-lectin interaction and that this physical association is necessary for collaboration (23). Recent studies have shown that integrins can activate the p38 MAPK pathway and that · v integrin, p38 MAPK and uPA are functionally linked in breast cancer cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, uPAR can form a complex with ␤ 1 or ␤ 2 integrins to modulate their adhesive functions and with the ␤ 2 integrin, CR3 (CD11b/CD18), to trigger urokinase plasminogen activator-induced Ca 2ϩ fluxes in neutrophils (32,33). More recently, a signaling partnership between uPAR and L-selectin (CD62L) was also demonstrated in human polymorphonuclear neutrophils (34). More importantly, recent evidence suggests that C1q and mannose-binding lectin can engage cell surface calreticulin (cC1q-R) and CD91 to initiate macropinocytosis and uptake of apoptotic cells (35).…”
Section: Discussionmentioning
confidence: 99%